Models for linking hunter retention and recruitment to regulations and game populations - McGowan, C. P.; Price Tack, J. L.; Silvano, A. L.; Grand, J. B. (Frontiers in Conservation Science, 2023)
Declining hunter populations across North America present wildlife management agencies with the prospect of declining revenues for wildlife conservation and management and the need for new tools to evaluate management strategies and predict future status of game species and hunters. Here we present a modeling framework to link future hunter population dynamics to deer abundance, harvest success, and regulatory restrictiveness. Our model demonstrates that managers might face tradeoffs between managing for deer population abundance and hunting revenue and clarifies how these factors might affect decision making. We simulated three scenarios of restricted harvest, moderate harvest and liberal harvest and show that even though liberal harvest predicts higher cumulative license sales revenue, it corresponds with a decline in buck abundance over 20 years. In contrast, highly restrictive harvest corresponds with deer population growth, but a near collapse of hunter populations. Our hunter model is parameterized based on the authors' judgment and can be used for demonstration purposes. The utility of our tool would be dependent on accessing data on hunter retention and recruitment. However, these simulations demonstrate that these tools could be used to evaluate management strategies but also highlight uncertainties, establish research priorities, and potentially design an adaptive management framework.